Professional buyers guide, 1999-2000. (Manila Pacific Trade Media Publications, 2000)
Contents: Government/associations, suppliers profile, buyers' guide, services.
urpose: A directory for purchasing and material managers in discovering suppliers and service providers. It also has sections for governments and associations, as well as buyers.
Keywords: Philippines -- Manufacturers -- Directories; Industries -- Philippines -- Directories; Commercial products -- Philippines -- Directories; Service industries -- Philippines -- Directories; Purchasing